Charged pyridinium oximes with thiocarboxamide moiety are equally or less effective reactivators of organophosphate-inhibited cholinesterases compared to analogous carboxamides. (31st December 2022) - Kohoutova, Zuzana; Malinak, David; Andrys, Rudolf; Svobodova, Jana; Psotka, Miroslav; Schmidt, Monika; Prchal, Lukas; Musilek, Kamil
Abstract: The organophosphorus antidotes, so-called oximes, are able to restore the enzymatic function of acetylcholinesterase (AChE) or butyrylcholinesterase (BChE) via cleavage of organophosphate from the active site of the phosphylated enzyme. In this work, the charged pyridinium oximes containing thiocarboxamide moiety were designed, prepared and tested. Their stability and p Ka properties were found to be analogous to parent carboxamides (K027, K048 and K203). The inhibitory ability of thiocarboxamides was found in low µM levels for AChE and high µM levels for BChE. Their reactivation properties were screened on human recombinant AChE and BChE inhibited by nerve agent surrogates and paraoxon. One thiocarboxamide was able to effectively restore function of NEMP- and NEDPA-AChE, whereas two thiocarboxamides were able to reactivate BChE inhibited by all tested organophosphates. These results were confirmed by reactivation kinetics, where thiocarboxamides were proved to be effective, but less potent reactivators if compared to carboxamides.